A smart MnO2-doped graphene oxide nanosheet for enhanced chemo-photodynamic combinatorial therapy via simultaneous oxygenation and glutathione depletion - Peng Liu; Xin Xie; Miao Liu; Shuo Hu; Jinsong Ding; Wenhu Zhou (Elsevier, 2021)
The combination of chemotherapy and photodynamic therapy provides a promising approach for enhanced tumor eradication by overcoming the limitations of each individual therapeutic modality. However, tumor is pathologically featured with extreme hypoxia together with the adaptable overexpression of anti-oxidants, such as glutathione (GSH), which greatly restricts the therapeutic efficiency. Here, a combinatorial strategy was designed to simultaneously relieve tumor hypoxia by self-oxygenation and reduce intracellular GSH level to sensitize chemo-photodynamic therapy. In our system, a novel multi-functional nanosystem based on MnO2-doped graphene oxide (GO) was developed to co-load cisplatin (CisPt) and a photosensitizer (Ce6). With MnO2 doping, the nanosystem was equipped with intelligent functionalities: (1) catalyzes the decomposition of H2O2 into oxygen to relieve the tumor hypoxia; (2) depletes GSH level in tumor cells, and (3) concomitantly generates Mn2+ to proceed Fenton-like reaction, all of which contribute to the enhanced anti-tumor efficacy. Meanwhile, the surface hyaluronic acid (HA) modification could facilitate the targeted delivery of the nanosystem into tumor cells, thereby resulting in amplified cellular toxicity, as well as tumor growth inhibition in nude mice model. This work sheds a new light on the development of intelligent nanosystems for synergistic combination therapy via regulating tumor microenvironment.